Changes in the bacterial community in the fermentation process of kôso, a Japanese sugar-vegetable fermented beverage. Issue 2 (1st February 2017) - Chiou, Tai-Ying; Suda, Wataru; Oshima, Kenshiro; Hattori, Masahira; Takahashi, Tomoya
Abstract: Kôso is a Japanese fermented beverage made with over 20 kinds of vegetables, mushrooms, and sugars. The changes in the bacterial population of kôso during fermentation at 25 °C over a period of 10 days were studied using 454 pyrosequencing of the 16S rRNA gene. The analysis detected 224 operational taxonomic units (OTUs) clustered from 8 DNA samples collected on days 0, 3, 7, and 10 from two fermentation batches. Proteobacteria were the dominant phylum in the starting community, but were replaced by Firmicutes within three days. Seventy-eight genera were identified from the 224 OTUs, in which Bifidobacterium, Leuconostoc, Lactococcus, and Lactobacillus dominated, accounting for over 96% of the total bacterial population after three days' fermentation. UniFrac–Principal Coordinate Analysis of longitudinal fermented samples revealed dramatic changes in the bacterial community in kôso, resulting in significantly low diversity at the end of fermentation as compared with the complex starting community. Graphical abstract: : Changes in the relative abundance of the 50 species in kôso communities during 10-day fermentation.